If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(3*(x-7))/2 = 15 // - 15
(3*(x-7))/2-15 = 0
(3*(x-7))/2+(-15*2)/2 = 0
3*(x-7)-15*2 = 0
3*x-51 = 0
(3*x-51)/2 = 0
(3*x-51)/2 = 0 // * 2
3*x-51 = 0
3*x-51 = 0 // + 51
3*x = 51 // : 3
x = 51/3
x = 17
x = 17
| (3.4x)+7=x+54.6 | | 2x+4x-9+x^2+2x+9=180 | | 0=x^2+13x+30 | | 13n=.26 | | 3x-1=0.50(4x+6) | | 6x^2+36+48=0 | | -7x-8=4x+6 | | 4/13p=-16/5 | | -8/3÷3 | | -18=0(-3)+b | | -5/6(6)=x | | -17=0(-2)+b | | -21x+7=14 | | 550-30y/50 | | -5/6y=1 | | M=-0.711A+206.6 | | 1.50b=31.50 | | 2x^2=-21x | | -3.5x=9.2 | | 5/6x72/5 | | 17=0(-2)+b | | -5/6y=0 | | 21x(2/7)=6 | | -4.3x=-8.6 | | F(x)=x^4-4x^3-9x^2+36 | | 0.2x-0.5x-3=18 | | -3x-14=y | | y^2+54=0 | | 17+33x=5 | | -3x+7(2)=-16 | | -x=59 | | 5t-9t+1t=0 |